(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Parenteral nutrition (PN) is defined as IV. PP can be administered through a peripheral or central venous device, depending on the osmolarity of the solution. Peripheral PP can be administered through a peripheral venous access device. The osmolarity of the solution should be ≤ 900 mOsm/L. A solution with a higher osmolarity can lead to thrombophlebitis. Central PN requires a central venous access device for safe infusion, as the osmolarity of solutions intended for central PN is > 900 mOsm/L.